(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Given the time-consuming and costly measurement of heat-moisture comfort indexes and the difficulty of quantifying contact comfort, 20 sports fabrics were tested for air permeability, moisture permeability, thermal resistance, moisture resistance, sensory evaluation indicators and 18 mechanical parameters. Then, the correlation between contact comfort indexes and mechanical parameters was analysed. On this basis, multiple linear regression prediction models for thermal resistance, moisture resistance and contact comfort indexes of sports fabrics were established. The results show that the thermal resistance of sports fabrics can be predicted by Compression work (CW) and Compression recovery rate (CRR) indicators, and the moisture resistance can be predicted by Bending work in the warp (BWa) and CRR indicators. The smoothness of sports fabrics can be predicted by CW and Compression stiffness (CAR), the softness by Bending work in weft (BWe) and CAR, the warmth by CW, BWe and Surface friction coefficient in weft (SFCe), and the combined feeling by Bwe and CAR. The models were also validated and are considered to have practical implications for companies and consumers when assessing and improving the comfort of sports fabrics.